The Concept of the Perfect Human (al-Insān al-Kāmil) in Ibn Arabi’s Thought - Syeda Dur e Nayab; Md. Mahdi Hassan (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The idea of al-Insān al-Kāmil (the Perfect Human) is central to the mystical thought and religious system of Ibn ʿArabi. As the realization and final point of creation, the Perfect Human is the mirror where all of God's attributes are completely expressed, equilibrated, and realized. No purely metaphysical conception, it manifests an integrated perception of reality where the human individual is both microcosm of the universe and intercessor between the Divine and the universe. This article delves into the ontological, epistemological, and metaphysical levels of the Perfect Human in the thinking of Ibn ʿArabi and uses mainly his two foundational writings, Fusūs al-Ḥikam and al-Futūḥāt al-MakkiyyaIt explains how the manifestation of God (tajalli), the Unity of Being (waḥdat al-wujūd), and the interdependence of prophethood and sainthood are all components of the concept of the Perfect Human. The book also mentions contemporary concepts of this belief, thinking about it in terms of its potential application to spirituality debates in the modern world, selfhood, ethics, and cosmology. By investigating both classical expositions and modern scholarly debates, this article aims to highlight the enduring significance of Ibn ʿArabi’s vision of human potential, divine proximity, and universal harmony. Ultimately, the Perfect Human is presented not just as an esoteric ideal but as a dynamic model for spiritual realization, ethical living, and transformative engagement with the world.